Pengaruh Kinerja Keuangan Terhadap Pertumbuhan Ekonomi Inklusif Melalui Human Development Index - Widodo, Dhian Puteri; Isnowati, Sri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to examine the effect of financial performance on inclusive economic growth through the human development index in Central Java Province. There are 35 districts / cities that are sampled with a period of five years, namely 2018-2023. In this study, financial performance is measured by regional financial independence, regional financial effectiveness, and harmonization of regional expenditures, while inclusive economic development is measured using the IPEI. This study was conducted with regression tests with a random effect approach and path analysis. The results show that financial performance in the form of the degree of fiscal decentralization, harmonization of regional expenditure has a significant positive influence on inclusive development and HDI. Meanwhile, the effectiveness of PAD has a significant positive effect on inclusive development but a significant negative effect on HDI. The results of path analysis show that HDI plays a significant mediating role between DDF, EFE, BO, and BM in relation to IPEI. HDI has a significant positive effect on IPEI with a p-value of 0.000, indicating that an increase in HDI promotes inclusive economic development. Indirectly, DDF, BO, and BM also show significant positive effects on IPEI through HDI, with p-values of 0.000, 0.000, and 0.0032 respectively. However, EFE shows a significant negative relationship with IPEI through HDI, with a p-value of 0.000, indicating the need for more effective management of PAD to support human development.